1967
DOI: 10.1901/jeab.1967.10-213
|View full text |Cite
|
Sign up to set email alerts
|

CLASSICAL CONDITIONING OF COURTING BEHAVIOR IN THE JAPANESE QUAIL, COTURNIX COTURNIX JAPONICA1

Abstract: Male Japanese quail were classically conditioned to display courting behavior at the sound of a buzzer, a previously neutral stimulus. The buzzer (conditioned stimulus) was paired with the presentation of a female quail (unconditioned stimulus) for a number of trials. The courting display, invariably elicited from the male by the presentation of the female, began to appear in part to the conditioned stimulus as early as the fifth pairing. All components of the display were elicited from all birds by the condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
3
3

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 3 publications
0
46
3
3
Order By: Relevance
“…In the first such study, Farris (1967) presented a buzzer to male quail just before giving them access to a sexually receptive female and found that the buzzer CS came to elicit courtship responses. Domjan, Lyons, North, and Bruell (1986) failed to replicate the conditioningof courtship behavior but found that males would approach and remain near an arbitrary visual CS (a light) that had been paired with sexual reinforcement.…”
Section: Sexual Conditioning With Arbitrary Cssmentioning
confidence: 99%
“…In the first such study, Farris (1967) presented a buzzer to male quail just before giving them access to a sexually receptive female and found that the buzzer CS came to elicit courtship responses. Domjan, Lyons, North, and Bruell (1986) failed to replicate the conditioningof courtship behavior but found that males would approach and remain near an arbitrary visual CS (a light) that had been paired with sexual reinforcement.…”
Section: Sexual Conditioning With Arbitrary Cssmentioning
confidence: 99%
“…Sexual conditioning in male Japanese quail was first investigated by Farris (1967), who reported that male quail perform a courtship-like action pattern, the horizontal display, in response to a brief buzzer that is presented just before the introduction of a female bird into their cage. The conditioned behavior included stretching the head and neck forward and slightly downward in a horizontal position.…”
Section: Response Considerations In Sexual Conditioningmentioning
confidence: 99%
“…Also, a gradual shift in their form during ontogeny, often from what is called "simple" to "more complex" has been suggested (e.g. VAN DE BURG, 1976;DANE et al, 1964;FARRIS, 1967;FISCHER, 1965;Fox, 1970;HENTY, 1966;KRUIJT, 1964;MOYNIHAN, 1959;PLATZ, 1974;WILEY, 1973;WILLIAMS, 1972;WYMAN & WARD, 1973 (1966,1969); strutting in turkey chickens: SCHLEIDT (1970); SCHULMAN (1970). ROGGENBRUCK (1986) and STAMPS (1978) studied the form development of displays in lizards in more detail and found adult-like displays in very young lizards.…”
mentioning
confidence: 99%